Isotopic Evidence for the Evolution of Subsurface Nitrate in the Western Equatorial Pacific. Issue 3 (2nd March 2018) - Lehmann, Nadine; Granger, Julie; Kienast, Markus; Brown, Kevin S.; Rafter, Patrick A.; Martínez‐Méndez, Gema; Mohtadi, Mahyar
Abstract: Subsurface waters from both hemispheres converge in the Western Equatorial Pacific (WEP), some of which form the Equatorial Undercurrent (EUC) that influences equatorial Pacific productivity across the basin. Measurements of nitrogen (N) and oxygen (O) isotope ratios in nitrate (δ 15 NNO3 and δ 18 ONO3 ), the isotope ratios of dissolved inorganic carbon (δ 13 CDIC ), and complementary biogeochemical tracers reveal that northern and southern WEP waters have distinct biogeochemical histories. Organic matter remineralization plays an important role in setting the nutrient characteristics on both sides of the WEP. However, remineralization in the northern WEP contributes a larger concentration of the nutrients, consistent with the older "age" of northern thermocline‐depth and intermediate‐depth waters. Remineralization introduces a relatively low δ 15 NNO3 to northern waters, suggesting the production of sinking organic matter by N2 fixation at the surface—consistent with the notion that N2 fixation is quantitatively important in the North Pacific. In contrast, remineralization contributes elevated δ 15 NNO3 to the southern WEP thermocline, which we hypothesize to derive from the vertical flux of high‐δ 15 N material at the southern edge of the equatorial upwelling. This signal potentially masks any imprint of N2 fixation from South Pacific waters. The observations further suggest that the intrusion of high δ 15 NNO3 and δ 18 ONO3 waters from the eastern margins is more prominent in the northern than southern WEP. Together, these north‐south differences enable the examination of the hemispheric inputs to the EUC, which appear to derive predominantly from southern hemisphere waters. Key Points: Remineralization adds 15 N‐enriched nitrate to the southern hemisphere thermocline at the southern edge of the equatorial Pacific upwelling Isotope tracers indicate the remineralization of 15 N‐depleted nitrate due to N2 fixation in the northern Pacific thermocline waters Mixing estimates suggest a predominantly southern hemispheric source to the Equatorial Undercurrent that supplies the equatorial Pacific upwelling